1988
DOI: 10.1212/wnl.38.8.1194
|View full text |Cite
|
Sign up to set email alerts
|

Results of anterior corpus callosum section in 24 patients with medically intractable seizures

Abstract: Twenty-four medically refractory seizure patients, who did not qualify for excisional surgery, had anterior two-thirds corpus callosum section. Three to 11 years' postoperative follow-up suggests that this procedure can (1) lateralize a frontal lobe focus, which may lead to subsequent localized excision and (2) significantly reduce seizure frequency and severity in 75% of the patients without giving any permanent neurologic deficits. Patients with an ictal focus confined to one frontal lobe did best (8/8 impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
4

Year Published

1991
1991
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(58 citation statements)
references
References 3 publications
4
49
4
Order By: Relevance
“…Section of the anterior two-thirds of the corpus callosum resulted in good seizure control in this patient population. Seizure control was similar to that which has been previously reported in the literature [2, 3, 5, 7, 8, 10, 12]. We propose that the use of such navigational and image-guided systems act as valuable intraoperative adjunct for the neurosurgeon performing corpus callosotomies.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Section of the anterior two-thirds of the corpus callosum resulted in good seizure control in this patient population. Seizure control was similar to that which has been previously reported in the literature [2, 3, 5, 7, 8, 10, 12]. We propose that the use of such navigational and image-guided systems act as valuable intraoperative adjunct for the neurosurgeon performing corpus callosotomies.…”
Section: Discussionsupporting
confidence: 85%
“…Since then, there has been some controversy as to which procedure is most effective. Some series report similar seizure control with complete and partial callosotomies [7, 8], while others advocate the use of a complete procedure [5, 9]. Some studies do acknowledge that such reported differences may relate to potential differences in the extent of anterior callosotomies [9].…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1960s numerous studies regarding the indication and outcomes of corpus callosotomies have been published [4,5,6,7,8,9]. The goal of a callosotomy procedure is to reduce the frequency and severity of seizures by interrupting common seizure spread pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Many investigators have reported the elimination or reduction of frequency as well as the severity of the drop attacks most effectively compared to any other seizure types. (Gates, Leppik et al 1984;Purves, Wada et al 1988;Nordgren, Reeves et al 1991;Spencer, Spencer et al 1993) Majority of patients with medically intractable seizures without localizing lesions undergoing callosotomy usually comprise of many different types of seizures. Infantile spasm, Lennox-Gastaut Syndrome, and West syndrome are the well known syndromic epilepsy with multiple seizure types that are good candidates for the callosotomy.…”
Section: Indicationmentioning
confidence: 99%
“…Purves et al supported the anterior callosotomy alone is sufficient for some patients controlling www.intechopen.com Corpus Callosotomy in Pediatric Intractable Epilepsy: Microsurgical Technique,Implication and Variation 135 seizure. (Purves, Wada et al 1988) However, the seizure outcome is far better in total callosotomy compared to partial callosotomy in many series especially in pediatric patients without concerned neuropsychological complications. (Rathore, Abraham et al 2007) We had the same 2-stage callosotomy principle previously as well.…”
Section: The Debate On Extent Of Callosotomymentioning
confidence: 99%